Pressupostos epistemológicos e a experimentação no ensino de Química: o caso de Lavoisier - Prado, Letícia do [UNESP] (2015)
This work aims to investigate the role of the experimentation in the history of chemistry and in teaching of some specific contents of this particular science, in order to describe the potentialities and the limits of experimentation in its teaching today. For this, we described in Chapter I discussion on the role of experience and experimentaion for some philosophies/epistemologies between the seventeenth to twentieth centuries. We used as reference the works of Bacon. Hume, Comte, Bachelard, Popper, and Kuhn. In Chapter II we developed a research about the history of experimentation in chemistry, talking as a singular reference studies that Lavoisier made in the eighteenth century in the Elements of Chemistry. In Chapter III we made an overview of the use of experimentation in the history of the Chemistry Teaching in Brazil, ending our considerations with the educational reforms that generated new parameters and academic papers on the use of experimentation. For the chapters, we employed the internalist analysis of text as a methodology of study. In Chapter IV, we conducted a survey of experimental proposals contained, in the textbooks proposed by the National Textbooks Program for Secundary Education in the year of and we analyzed as to the epistemological assumptions about experimentation. The experiments found were analyzed regarding the teacher's planning issues, experimentation mode an feedback of the students included in all proposals for experimentation activities. At the end of this first analysis they were analyzed with the intention of tracing the trial conceptions that constituted them, we search for experiments and excerpts from books that addressed the Lavoisier's work. They were analyzed with the intention of tracing the trial conceptions that constituted them. For this step we used the content analysis as a methodology of study. Our final aim whith this study was to establish the limits and potentialities of the use of...